IFRS ADOPTION AND EARNINGS MANAGEMENT IN BRAZILIAN PUBLICLY TRADED COMPANIES - Roberto Midoguti Joia; Silvio Hiroshi Nakao (Revista de Educação e Pesquisa em Contabilidade, 2014)
In 2007, Brazil adopted the International Financial Reporting Standards (IFRS). Studies involving publicly traded companies in different countries around the world indicate that these new standards tend to improve the information quality and make it more comparable and transparent. This study was aimed at verifying any changes in the earnings management levels after 2010 and whether this happened in function of the full adoption of the IFRS by the Brazilian publicly traded companies (except for financial institutions). The data were extracted from the three-monthly financial statements of the databases from Economática and the Brazilian Securities Commission for the period from 2006 till 2011. To achieve the research objectives, two tests were applied. The first showed that the average discretionary accruals, calculated through the Modified Jones Model, were lower after 2010. Next, the regression analysis was elaborated, using panel data with Newey-West’s correction. The results did not confirm the hypothesis that the adoption of the IFRS affected the earnings management level in the period under analysis, but showed that the size and indebtedness significantly explain the discretionary accruals, independently of the adoption of the IFRS. The results suggest that larger companies with a large proportion of own capital tend to produce higher quality reports, independently of the adoption of the IFRS.